Epidemiology, comorbidities, and prescription patterns of Korean Prurigo nodularis patients: A multi-institution study - Woo, Yu Ri; Wang, Sehee; Sohn, Kyung Ah; Kim, Hei Sung (Journal of Clinical Medicine, 2022)
Prurigo nodularis (PN) is a chronic dermatosis typified by extraordinarily itchy nodules. However, little is known of the nature and extent of PN in Asian people. This study aimed to describe the epidemiology, comorbidities, and prescription pattern of PN in Koreans based on a large dermatology outpatient cohort. Patients with PN were identified from the Catholic Medical Center (CMC) clinical data warehouse. Anonymized data on age, sex, diagnostic codes, prescriptions, visitation dates, and other relevant parameters were collected. Pearson correlation analysis was used to calculate the correlation between PN prevalence and patient age. Conditional logistic regression modeling was adopted to measure the comorbidity risk of PN. A total of 3591 patients with PN were identified at the Catholic Medical Center Health System dermatology outpatient clinic in the period 2007–2020. A comparison of the study patients with age-and sex-matched controls (dermatology outpatients without PN) indicated that PN was associated with various comorbidities including chronic kidney disease (adjusted odds ratio (aOR), 1.48; 95% confidence interval (CI), 1.29–1.70), dyslipidemia (aOR, 1.88; 95% CI, 1.56–2.27), type 2 diabetes mellitus (aOR, 1.37; 95% CI, 1.22–1.54), arterial hypertension (aOR, 1.50; 95% CI, 1.30–1.73), autoimmune thyroiditis (aOR, 2.43; 95% CI, 1.42–4.16), non-Hodgkin’s lymphoma (aOR, 1.95; 95% CI, 1.23–3.07), and atopic dermatitis (aOR, 2.16, 95% CI, 1.91–2.45). Regarding prescription patterns, topical steroids were most favored, followed by topical calcineurin inhibitors; oral antihistamines were the most preferred systemic agent for PN. PN is a relatively rare but significant disease among Korean dermatology outpatients with a high comorbidity burden compared to dermatology outpatients without PN. There is great need for breakthroughs in PN treatment.
Keywords: Comorbidities; Epidemiology; Korea; Prescription pattern; Prurigo nodularis